GEREJA BERMISI MELALUI MEDIA DIGITAL DI ERA REVOLUSI INDUSTRI 4.0 - Yosua Feliciano Camerling; Mershy Ch. Lauled; Sarah Citra Eunike (VISIO DEI: JURNAL TEOLOGI KRISTEN, 2020)
The purpose is to describe the role of the media in supporting missions in the fourth industrial revolution. The cause of several studies found there are still some digital media users who are not wise in social media. One example is the outbreak of hate speech that played a more significant role in racial crime in 2019. Also, few social media and online communication users use their accounts to slander, bully, and spread fake news. For this reason, users must choose wisely in using their social media accounts. The method used is qualitative by collecting several references from library studies to produce several explanations that are discussed systematically. The results of this study indicate that the church needs to open up in terms of media development because this will be one of the most effective investments in protecting lives in the era of the fourth industrial revolution. Some strategies to communicate the gospel message that can intensify media services include live streaming sermons, recording sermon videos, and updating status through Facebook and Instagram. The conclusion is that media services are beneficial to reach every community but is challenging to achieve. But most of all, media service can aim to speed up the second coming of Jesus Christ. “And this gospel of the kingdom shall be preached in all the world for a witness to all nations; and then shall the end come.” (Matthew 24:14 - NKJV).